ANALYSIS OF LEAD CONTENT IN LIPSTICKS SOLD IN BANDA ACEH USING SPECTROPHOTOMETRY - Nasir, M; Khaldun, Ibnu; Mauliana, Ulfa (FKIP USK, 2024)
Lipstick is a widely used cosmetic product, particularly among women, designed from solid-based materials containing dissolved or suspended colorants that meet regulatory standards. Ensuring lipstick products are free from heavy metals, especially lead, is crucial as ingestion through food or drink is possible. According to BPOM regulations, the permissible lead content in cosmetics is 20 mg/kg or 20 mg/L (20 ppm). This study aimed to analyze the lead content in various lipstick products using UV-Vis spectrophotometry and validate the method's reliability through parameters such as accuracy, precision, linearity, limit of detection (LoD), and limit of quantification (LoQ).The methodology involved the use of Alizarin Red S as a complexing agent. Accuracy was determined at 99.21%, precision ranged from 0.1973% to 2.3905%, linearity was measured at 0.9986, and the LoD and LoQ values were 0.0726 ppm and 0.2420 ppm, respectively. The lead concentrations in local red lipstick, local peach lipstick, imported red lipstick, imported peach lipstick, and Arabic-style lipstick were 4.4831 ppm, 3.2675 ppm, 3.4701 ppm, 2.4675 ppm, and 2.4312 ppm, respectively. These findings confirm that all samples fall well below the maximum allowable lead concentration of 20 ppm as stipulated by BPOM.In conclusion, the tested lipsticks are considered safe for use in terms of lead content. This study underscores the importance of regular monitoring and stringent quality control in cosmetic production to ensure consumer safety.